A política na ontologia de Lukács: um debate contemporâneo - Paixão, Bruno Gonçalves da (2021)
This thesis aims to analyze the category of politics in the last stage of production of the Hungarian philosopher György Lukács, that is, in the period in which his production turns to an ontological-materialistic quality. In this regard, it will be searched, especially, the Ontology of Social Being, and the ideology complex in it. Thus, the interest will be focused on investigating the social function of politics in the general structure of social being, as well as its entailment in broad or strict ideology, and, at the same time, whether politics, in the structure of the new complex of being (social), would be an ineliminable mediation of social being or not. That's because, if politics is a universal and eternal mediation of social being, it would indicate that the political dimension was and is necessary to all forms of economic and social organization. In the other extreme, in case of politics, for Lukács, have its genesis since the Neolithic Revolution, such a category could play another role in the structure of social being, because its emergence would be linked to the newborn class society, which is enabled by a new social relationship: the appropriation of the labor of others (private property). In the latter case, politics would be an expression of class society, with a special characteristic of being a sphere aimed at the domination of one class over another. That is to say, the social function of ensuring the exploitation of man by man would lie with politics. And precisely because of that, as the result of the research suggests, the politics complex would have a predominantly negative characteristic, that is, superfluous to a classless Society.